written 7.7 years ago by
teamques10
★ 66k

•
modified 7.7 years ago

The functional dependencies satisfied by the relation are as follows:
A → B
For the tuples t1(A1,B1,C1) and t2(A1,B1,C2), t1 (A) =t2(A)=A1 and t1(B)=t2(B)=B1. Thus, the functional dependency A→B is satisfied by the relation.
C → B
For the tuples t1(A1,B1,C1) and t3(A2,B1,C2), t1 (C) =t3(C) =C1 and t1 (B)=t3(B)=B1. Thus, the functional dependency C→B is satisfied by the relation.
 The dependency AC→B can also be obtained.
Following are the functional dependencies which are not satisfied.
 C does not functionally determine A because the tuples t1(A1,B1,C1) and t3(A2,B1,C1) have the same C but different A values.
 The same tuples also show B does not functionally determine A.
 A does not functionally determine C because the first two tuples t1(A1,B1,C1) and t2(A1,B1,C2)have the same A value and different C values.
 The same tuples also show B does not functionally determine C.